La mobilité interprovinciale de la main-d’oeuvre au Canada : le cas de l’Ontario, de la Nouvelle-Écosse et du Nouveau-Brunswick - Cousineau, Jean-Michel (L'Actualité économique, 1979)
This paper studies the migratory flows between Ontario and two Atlantic provinces of Canada, from 1960-61 to 1975-76. Search theory is used as the theoretical framework and leads to predictions as to the influence on interprovincial migratory flows of three economic variables: relative wages, employment opportunities, and unemployment insurance (UI). Proxies for these theoretical variables are used in an ordinary least squares regression based on pooled time series and cross-section data on interprovincial migration in Canada (Family Allowances' data base). The model performs poorly in explaining short term variations in the interprovincial migration rates, and the expected return migration from Ontario to New Brunswick and Nova Scotia due to UI changes in 1971 is not found. However, the model performs relatively well in explaining long term interprovincial migration flows and the 1970's reversal of the net migratory flows between Central Canada (Ontario) and the Atlantic provinces considered. Higher unemployment rates in Ontario, improved relative wages in New Brunswick and Nova Scotia as well as the UI revisions of 1971 explain a significant part of the observed change.